LA-ICP-MS U–Pb dating of calcite cement in Upper Triassic tight-gas sandstone reservoirs, western Sichuan Basin, SW China - Yu, Y.; Lin, L.; Li, Zhen; Rankenburg, Kai; Evans, Noreen; McInnes, Brent (WILEY, 2022)
The absolute timing of carbonate cement formations can provide insights into porosity evolution and hydrocarbon accumulation in reservoirs. In this study, scanning electron microscopy-based cathodoluminescence (SEM-CL), quantitative mineralogical analysis and laser ablation inductively coupled plasma-mass spectrometry U–Pb dating were performed on calcite cements from sandstones in the fourth member of the Upper Triassic Xujiahe Formation in the western Sichuan Basin. Two samples yielded U–Pb ages of 149.5 ± 31.1 Ma and 190.0 ± 180.5 Ma (2σ), suggesting late diagenetic precipitation of calcite cements. The backscattered electron and SEM-CL images indicated that the cements precipitated after feldspar dissolution. Combined with palaeo-temperature evolution, these results suggest that the timing of calcite cement precipitation occurred between the Late Jurassic to Early Cretaceous. Rapid accumulation of sediment in the western basin in response to the Yanshanian Orogeny may have caused stratum overpressure, resulting in geofluid activity and calcite precipitation in the Xu4 sandstone.